2018
DOI: 10.1002/2211-5463.12354
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of miR‐193a‐3p in non‐small cell lung cancer and its potential molecular mechanism explored in silico using RNA‐sequencing and microarray data

Abstract: miR‐193a‐3p is a tumor‐related miRNA playing an essential role in tumorigenesis and progression of non‐small cell lung cancer (NSCLC). The objective of the present study was to investigate the relationship between miR‐193a‐3p expression and clinical value and to further explore the potential signaling of miR‐193a‐3p in the carcinogenesis of NSCLC. RNA‐sequencing and microarray data were collected from the databases GEO, ArrayExpress and The Cancer Genome Atlas (TCGA). Furthermore, in silico assessments were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Lung cancer (LC) has become an important etiology of malignant mortality worldwide [1]. Approximately 1.37 million deaths annually worldwide have been attributed to LC, and LC is a significant cause of cancer-related deaths in China [2, 3]. LC is divided into several different categories, such as lung adenocarcinoma, squamous cell lung carcinoma, large cell carcinoma and small cell lung carcinoma (SCLC) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer (LC) has become an important etiology of malignant mortality worldwide [1]. Approximately 1.37 million deaths annually worldwide have been attributed to LC, and LC is a significant cause of cancer-related deaths in China [2, 3]. LC is divided into several different categories, such as lung adenocarcinoma, squamous cell lung carcinoma, large cell carcinoma and small cell lung carcinoma (SCLC) [4].…”
Section: Introductionmentioning
confidence: 99%
“…A previously published study has identified abnormally expressed genes in LUAD based on TCGA data (Deng et al, 2018). Significantly altered microRNAs (miRs/miRNAs) were also identified, that were found to exert important functions as oncogenes or tumor suppressors (Gao et al, 2018; Liu et al, 2017). Compared with miRNAs, the discovery of LUAD-associated lncRNAs are still at a preliminary stage, but it has been demonstrated that they serve diverse and complex roles in tumorigenesis (Klingenberg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 6 Subsequently, the 3p arm of miR-193a (miR-193a-3p) was demonstrated as the biologically active entity in tumor cell-based assays. A large body of evidence in the literature clearly shows that miR-193a-3p is frequently downregulated in malignant cells, including hepatocellular carcinoma (HCC), 7 non-small cell lung cancer (NSCLC), 8 and triple negative breast cancer (TNBC). 9 Significant evidence points toward a strong tumor-suppressive function of miR-193a-3p.…”
Section: Introductionmentioning
confidence: 99%